Choosing to be a defender or an outsider in a school bullying incident: Determining factors and the defending process. (June 2016) - Chen, Li-Ming; Chang, Lennon Y.C.; Cheng, Ying-Yao
This study examined the determinants of students' willingness to intervene in bullying incidents, as well as the process underlying students' defending behaviors. The participants were 24 students (12 defenders and 12 outsiders) recruited from six secondary schools in southern Taiwan. The study used semi-structured interviews to collect qualitative data and a grounded theory approach to analyse the data. The results showed that bystanders in bullying situations tended to assess the perceived severity of a bullying incident, personal responsibility, affective factors, victim characteristics, relationship with the victim, and other factors before committing to an intervention. This study found four possible phases of defending behavior: a) personal assessment affects a bystander's decision to act as a defender or an outsider; b) a defender evaluates the severity of a situation and the relationship with the bully to determine strategies for defending; c) defenders who come forward to intervene are interrogated or threatened by bullies; and d) defenders then reassess whether to intervene again. The results of this study suggest that bystander intervention programs can encourage students' personal responsibility, awareness of the severity of school bullying, improvement of interpersonal relationships, and self-efficacy to raise bystanders' willingness to defend a victim.